Influence of water hardness on the process of fermentation by Medusomyces gisevii consortium - Dulka, Olha; Prybylskyi, Vitalii; Fedosov, Oleksii; Prokopyshyn, Serhii (My University, 2023)
Проведено дослідження впливу показників води на процес ферментації безалкогольного напою консорціумом Medusomyces gisevii

A study of the influence of water parameters on the process of fermentation of a soft drink by a consortium of Medusomyces gisevii was carried out
Keywords: кафедра готельно-ресторанної справи; ферментовані безалкогольні напої; чайний гриб; Medusomyces gisevii; вода; non-alcoholic fermented drinks; kombucha; water